Reducing Opioid Prescriptions after Common Outpatient Pediatric Urologic Surgeries: A Quality Improvement Assessment. Issue 1 (16th January 2023) - Stout, Megan; Alpert, Seth; Kersey, Kelly; Ching, Christina; Dajusta, Daniel; Fuchs, Molly; McLeod, Daryl; Jayanthi, Rama
Abstract : Introduction: Pediatric patients undergoing outpatient surgeries often receive prescriptions for postoperative pain, including opioid medications. As a result, the American Academy of Pediatrics formally challenged all pediatric surgeons to decrease opioid prescribing for common specialty-specific outpatient procedures at discharge. To meet this challenge, we designed a quality improvement project to decrease the average number of opioid doses administered to pediatric patients undergoing 3 common outpatient urologic surgeries: circumcision, orchiopexy, and inguinal hernia repair (IHR). Methods: We formally challenged providers at our institution to reduce opioid doses per prescription and administration to patients overall. We performed a retrospective chart review at our single pediatric institution to establish baseline opioid prescribing values from July 2017 to March 2018. We aimed to reduce this value by 50% in 6 months and sustain this decrease throughout the project duration. Results: We performed 1, 518 orchiopexies, 1, 505 circumcisions, and 531 IHRs. The percent change in the average number of opioid doses prescribed per patient from baseline values assessed to 2021 was statistically significant for orchiopexies ( P < 0.0001), IHRs ( P < 0.0001), and circumcisions ( P < 0.0001). In addition, the change in the percentage of patients prescribed opioids from baseline was statistically significant for all 3 procedures ( P < 0.001). Conclusions: This project demonstrated that through an organized quality improvement initiative, the average number of opioid medications prescribed and the total percentage of patients prescribed opioids following common outpatient pediatric urologic procedures can be decreased by at least 50% and sustained through project duration.